Regenerative Repair of Volumetric Muscle Loss Injury is Sensitive to Age - Kim, John T. (Tissue Eng Part A, 2020)
In this study, the influence of age on effectiveness of regenerative repair for the treatment of volumetric muscle loss (VML) injury was explored. Tibialis anterior (TA) VML injuries were repaired in both 3- and 18-month-old animal models (Fischer 344 rat) using allogeneic decellularized skeletal muscle (DSM) scaffolds supplemented with autologous minced muscle (MM) paste. Within the 3-month animal group, TA peak contractile force was significantly improved (79% of normal) in response to DSM+MM repair. However, within the 18-month animal group, muscle force following repair (57% of normal) was not significantly different from unrepaired VML controls (59% of normal). Within the 3-month animal group, repair with DSM+MM generally reduced scarring at the site of VML repair, whereas scarring and a loss of contractile tissue was notable at the site of repair within the 18-month group. Within 3-month animals, expression of myogenic genes (MyoD, MyoG), extracellular matrix genes (Col I, Col III, TGF-β), and key wound healing genes (TNF-α and IL-1β) were increased. Alternatively, expression was unchanged across all genes examined within the 18-month animal group. The findings suggest that a decline in regenerative capacity and increased fibrosis with age may present an obstacle to regenerative medicine strategies targeting VML injury. IMPACT STATEMENT: This study compared the recovery following volumetric muscle loss (VML) injury repair using a combination of minced muscle paste and decellularized muscle extracellular matrix carrier in both a younger (3 months) and older (18 months) rat population. Currently, VML repair research is being conducted with the young patient population in mind, but our group is the first to look at the effects of age on the efficacy of VML repair. Our findings highlight the importance of considering age-related changes in response to VML when developing repair strategies targeting an elderly patient population.